The Effect Of Utilizing The Internet As A Source Of Learning History On The Learning Motivation Of Students In Class Xi Ips Man 1 Agam In The Year 2022 - Zuryati Zuryati (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2023)
This research raises the problem: 1) How is the utilization of the internet as a source of learning history by students of class XI IPS MAN 1 Agam in the 2022/2023 academic year? And 2) Is there an influence of the utilization of the internet as a source of learning history on the learning motivation of students in class XI IPS MAN 1 Agam in the 2022/2023 academic year? The purpose of this research is to find out: 1) To determine the utilization of the internet as a source of learning history by students of class XI IPS MAN 1 Agam in the 2022/2023 academic year, and 2) To determine the effect of internet utilization as a source of learning history on learning motivation of students in class XI IPS MAN 1 Agam Lesson Year 2022/2023. The results obtained from this study are the utilization of the internet as a learning resource in the good enough category while student learning motivation is in the high category. From the results of regression analysis, the value of Fcount = 19.607 with a significance of 0.000 <0.05 shows that there is an effect of internet utilization as a learning resource on the learning motivation of students in class XI IPS MAN 1 Agam in the 2022/2023 academic year.